Gatilhos de problema e seus efeitos na interpretação simultânea de Libras para português: um estudo sobre informações numéricas e datilológicas - Luciene de Macedo Gomes Viana (2022)
Brazilian Sign Language (Libras) interpreters deal daily with the task to reformulate messages between a spoken and a signed language. This interpreting task is, most of the time, simultaneous; in such a way that the interpreter needs to comprehend the message in the source language and, based on this single exhibition (whether visual or auditory), storage and produce this message in the target language – during a short period of time. Libras interpreters also face the challenge to interpret between languages that are in different modalities. Simultaneous interpreting between languages in different modalities, also known as cross-modal or intermodal interpreting, has been investigated by different researchers who are interested in the effects of the modality in the interpreting task. To put it differently, these works aim to discuss the effects of whether the interpreter is working from the spoken language into the signed language – signed interpreting – or whether the task is from the signed language into the spoken language – voice interpreting. Although there are some works on voice-interpreting, this direction is considerably less investigated than signed interpreting. Therefore, this is the direction we investigate in this dissertation. Assuming the concept of problem triggers in simultaneous interpreting (GILE, 2009, 2011), we discuss how they impact voice-interpreting from Libras to Portuguese. More specifically, we investigate how numbers and numerical information and also fingerspelling can be problem triggers and have negative effects in the interpreter’s delivery. In order to do that, we analyze interpretations given by professional interpreters. From this piece of data, we identified errors and omissions in the interpretations and also pauses and lengthening in the delivered message. These findings contribute to a better understanding of the problems Libras interpreters face when voice-interpreting.